Lipotoxicity and metabolic disorders at obesity - V. T. Ivashkin; M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss relation of obesity to phenomena of insulin resistance and lipotoxicity, and to demonstrate main therapeutic directions of their correction.Original positions. The most serious metabolic disorders related to obesity, include non-alcoholic fatty liver disease (NAFLD), diabetes mellitus, systemic hypertension with gradual development of heart failure, dyslipidemia, night apnea, etc. Recently scientists are more involved into the concept of limitation of fat tissue capacity to increase its volume as a factor associating obesity to metabolic syndrome and NAFLD. According to this hypothesis it is possible to explain phenomenon of severe obesity without development of metabolic complications. Within the same concept the role of differences in sets of nuclear receptors expressed in the liver of healthy persons and patients with NAFLD is taken into account. It is possible to explain lipotoxicity phenomenon as follows: in conditions of insulin resistance glucose stops to be an energy source and is substituted by lipolysis, therefore a plenty of free fatty acids is formed, having potential of toxicity and realizing metabolic disorders in target organs: the liver, the pancreas, muscles. New data on pathogenesis of metabolic disorders at obesity assume changes in comprehension of therapeutic actions. In 2008-2009 data on efficacy in treatment of insulin resistance and NAFLD of such pharmacological compounds, as glitazones, metformin, complex silibinin/phosphatidylcholine, ursodeoxycholic acid were published.Conclusion. In most cases the significant decrease of body mass is combined to resolution and better control over concomitant diseases. Recent studies demonstrated, that the visceral fat is in the higher degree associated to insulin resistance and the increased cardio-vascular risk while subcutaneous fat is metabolically more inert. In this aspect it is necessary to focus on glitazones (PPARs ligands), metformin among pharmacological substances, which has no influence on insulin secretion, however it has a lot of extrapancreatic effects by which it reduces increased concentrations of glucose in blood, improves tissue sensitivity to insulin and, thus, increases uptake of glucose by liver and muscles cells. In 2009 results of clinical and experimental researches which show significant efficacy of ursodeoxycholic acid at a dose of 30 mg/kg in treatment of non-alcoholic steatohepatitis and major therapeutic potential of silibinin and silibinin/phosphatidylcholine complex at non-alcoholic fatty liver disease were submitted.